Simultaneous Removal of Indomethacine, Papaverine and Allopurinol from Aqueous Solution by Using Submerged Aquatic Plant Nasturtium officinale - Okumus, Veysi; Oral, Elif; Basaran, Davut; Onay, Ahmet (Asian Journal of Chemistry, 2010)
Simultaneous removal of indomethacine, papaverine and allopurinol from aqueous solution by using submerged aquatic plant Nasturtium officinale biomass in high performance thin layer chromatography (HPTLC) was studied. Optimum biosorption conditions were determined as a function of contact time, pH, removal capacity of the amount of biomass and initial dry concentration. Experiments were performed in batch conditions. Concentrations of the drugs in the remaining solutions were simultaneously analyzed by HPTLC. Langmuir and Freundlich models were applied to describe the biosorption isotherm of the drugs by aquatic plant Nasturtium officinale biomass. According to the results, optimum parameters were found as 2.0 g biomass, pH:5.0 and 60 min contact time. Obtained from plots of Langmuir and Freundlich adsorption models, the highest drug uptakes were calculated from Langmuir isotherm and found to be 43.10, 39.68 and 38.61 mg/g for indomethacine, papa-verine and allopurinol, respectively.